HUBUNGAN PSIKOLOGIS IBU BERSALIN DENGAN KELANCARAN PROSES PERSALINAN KALA II DI RUMAH BERSALIN BHAKTI IBU SEMARANG - Shinta Ika Sandhi; Kurniawati Dwi Lestari (LPPM STIKES Muhammadiyah Kendal, 2021)
Maternal mortality rate is an indicator of the success of health services, especially midwifery. Until now, maternal mortality rates in Indonesia are still quite high. One of the causes of labor disruption is psychological factors, anxiety, fatigue, exhaustion and maternal worries, all combined so as to exacerbate existing physical pain. This type of analytic survey research using retrospective studies. The study was conducted at RB Bhakti Ibu Semarang. The population in this study were all maternity mothers in RB Bhakti Ibu with 65 respondents. The sampling technique uses random sampling and is obtained by 39 respondents. Hypothesis testing uses the analysis of chi square test to determine the psychological relationship of maternity mothers with the smoothness of the second stage of labor. The results showed that there was a psychological relationship between maternity mothers and the smoothness of the second stage of labor with a p value of 0,000.